Impact of high-pressure treatments on physicochemical and structural changes of reconstituted micellar casein concentrates from bovine and caprine milk: A comparative study - Khaled S. Nassar; Hala M. Bayomy; Eman S. Alamri; Nawal A. Ozaybi; Sameh A. Korma; Jiaping Lv; Eman S. Ragab (Journal of Dairy Science)
ABSTRACT: This study investigated the effect of high-pressure processing (HPP) on the physicochemical and structural changes in reconstituted micellar CN concentrates (MCC) sourced from bovine (BMCC) and caprine (CMCC) milk. When applying pressures ranging from 100 to 500 MPa for 30 min at 25 ± 2°C, it was observed that BMCC exhibited a notable increase in soluble minerals and solubility percentages with a simultaneous reduction in particle size and zeta potential compared with CMCC. In BMCC, Ca and P solubility rose from 27.71% and 33.02% to 90.33% and 92.01%, respectively. In CMCC, the solubility of Ca and P increased from 36.12% and 38.29% at 100 MPa to 52.57% and 56.77% at 500 MPa. Additionally, the reduction in particle size was more pronounced in BMCC, with a 53% decrease at 500 MPa, compared with a 19.90% reduction in CMCC. Furthermore, fluorescence intensity, indicative of surface hydrophobicity, decreased in BMCC samples (from 3,478 to 2,571 arbitrary units [a.u.]), whereas it increased in CMCC samples (from 2,388 to 4,058 a.u.) across the same pressure range. Comparative analysis revealed that HPP-treated CMCC samples exhibited a decline in α-helix content until the treatment at 300 MPa, followed by an increase post-treatment at 500 MPa. Additionally, a rise in β-sheet structure content was observed, except for the sample treated at 500 MPa, where β-sheet content significantly decreased. These findings suggest that HPP holds promise as a viable technological approach in the dairy sector for enhancing the functional characteristics of CMCC.